The ecosystem services of mangroves for sustainable coastal area and marine fauna in Lombok, Indonesia: A review - Pahmi Husain; Agil Al Idrus; Muhammad Shohibul Ihsan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2020)
Abstract: Mangroves are one of the coastal ecosystems with high productivity, and their associated biodiversity provides a range of ecosystem services. The aerial roots of mangroves partly stabilize this environment and give a substratum on which many species of plants and animals live. Above the water, the mangrove trees and canopy provide important habitat for a wide range of species. These include birds, insects, mammals, and reptiles. Below the water, the mangrove roots are overgrown by epibionts such as tunicates, sponges, algae, and bivalves. The soft substratum in the mangroves forms a habitat for various infaunal and epifaunal species. At the same time, the space between roots provides shelter and food for motile fauna, such as prawns, crabs, and fishes. Mangrove litter is transformed into detritus, which partly supports the mangrove food web. Plankton, epiphytic algae, and microphytobenthos also form an essential basis for the mangrove food web. Due to the high abundance of food and shelter, and low predation pressure, mangroves form an ideal habitat for a variety of animal species, during part or all of their life cycles. As such, mangroves may function as nursery habitats for (commercially important) crab, prawn and fish species, and support offshore fish populations and fisheries.